Identification of Microplastics in Euthynnus affinis in Kedonganan Area, Kuta, Badung, Bali - Ayu Saka Laksmita W; Desak Putu Risky Vidika Apriyanthi; Ni Putu Widayanti (Jurnal Ilmu Lingkungan, 2024)
Plastic waste pollution in the ocean can compromise food safety for the community in the world. One of the most dangerous polution today is microplastics. Microplastics are plastic particles that are ≤ 5 μm in size and cannot dissolve in water. Fish is one of the important foodstuffs that is often consumed by humans because, besides its delicious taste, fish also has good nutritional value. The presence of microplastic contamination in fish consumed by humans will certainly be very detrimental to humans. The purpose of this study was to determine the type and abundance of microplastics in fish Euthynnus affinis in the Kedonganan area, Kuta, Badung, Bali. This study was conducted from April to May 2023. The fish samples used were 30 samples with descriptive qualitative analysis. Microplastic particles were extracted first for further analysis. The results showed the types of microplastics found in Euthynnus affinis, namely film, fibre, and fragment types. While the abundance of microplastics in Euthynnus affinis, the fibre type is the most common type of microplastics found at 2.1 particles/individual followed by fragment and film types at 1.1 particles/individual and 0.8 particles/individual respectively.